Differential Changed Excitability of Spinal Motor Neurons Innervating Tibialis Anterior and Peroneus Muscles Cause Foot Inversion After Stroke - Liu, Gang; Chia, Chin-hsuan; Cao, Yue; Tang, Xin-wei; Tian, Shan; Shen, Xue-yan; Chen, Ying; Lu, Rong-rong; Wu, Jun-fa; Wu, Yi (Frontiers in Neurology, 2020)
Objective: To study differential post-stroke changes of excitability of spinal motor neurons innervating a group of antagonist muscles of ankle and their effects on foot inversion. Methods: F waves in tibialis anterior (TA) and peroneus muscles (PN) were recorded. The condition of spasticity and foot inversion in stroke patients were also evaluated. The differences of F wave parameters between patients and healthy controls (HC), as well as TA and PN, were investigated. Results: There were natural differences in the persistence of the F waves (Fp) and F/M amplitude ratio (F/M) between TA and PN in HC. Stroke patients showed significantly higher F/M in TA and PN, while there was no difference in Fp comparing to HC. The natural differences in F wave parameters between TA and PN were differentially retained after stroke. The natural difference of the two muscles in Fp remained unchanged and the F/M difference disappeared in those without spasticity or foot inversion, while the Fp difference disappeared and the F/M difference remained in those with spasticity or foot inversion. Conclusion: Based on the natural difference of the number and size of spinal motor neurons innervating TA and PN, their excitability may change differently according to the severity of the stroke, which may be the reason of foot inversion.